Success and failure using scenario planning to enhance organisational longevity. (9th December 2013) - Weitzman, Felix; Chermack, Thomas J.
Scenario planning has been linked to increased organisational ability to adapt to changed in the environment. The connection between scenario planning and organisational learning, awareness of the environment, human resources development (HRD), crisis readiness and management, and strategic planning are presented. The paper concludes despite many anecdotal cases and claims that scenario planning can help increase organisational survival, there is a lack of sufficient empirical research to support these claims.